EMM Project—LD GRIDS: Design of a Charged Dust Analyser for Moon Exploration - Diego Scaccabarozzi; Abdelrahman Mohamed Ragab M. Ahmed; Andrea Appiani; Bortolino Saggin; Carmen Porto; Francesca Esposito (Designs, 2025)
This work presents a comparative design of the sensing elements for the Lunar Dust GRID System (LD GRIDS), a dust analyser conceived to measure charged particles on future lunar missions. LD GRIDS replaces traditional electrodes with continuous conductive grids, i.e., the sensing elements of the instrument, which are able to collect induced charge when charged particles pass through them. The investigation focuses on evaluating the influence of various grid geometrical parameters (size, thickness, and patterns) on the sensor’s performance, either from an electrical or a mechanical perspective. All simulations were carried out using off-the-shelf numerical modelling software, where electrostatic simulation (i.e., induction performance), modal analysis, and quasi-static structural responses under a high acceleration quasi-static load were examined. The results indicate that while grids with round patterns tend to produce a higher induced charge, they also experience higher localised stresses compared to square pattern ones. Moreover, grid size does not significantly affect the instrument sensitivity, whereas increasing the grid thickness significantly reduces peak stresses, with only minor effects on electrostatic performance. Overall, the findings provided valuable insights for optimising the LD GRIDS design, aimed at balancing either electrostatic sensitivity or mechanical resistance, facing the harsh lunar environment.